Tantangan Transformasi Produk Digital Dalam Perbankan Syariah: Studi Kasus Bank Syariah Indonesia Kc Kupang - Mardiana Muslimin; Fransina W. Ballo; Novi Theresia Kiak (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Sharia banking digital product tranformation is a necessity because technological developments are increasingly rapid. This research aims to detemine the challenges of sharia bank digital product transformation. This research uses a qualitative approach, with data collection methods conducting interviews and documentation. The result of this research show that the challenges of digital product tranformation for sharia banks and sharia banks.however, BSI continues to update its system so that it can compete with coventional banks.